The Impact of Diaspora Remittances on Economic Growth: Evidence from Zimbabwe - Munanga, Makore Day (Graduate School of Business (GSB), 2021)
This research examined the impact of diaspora remittances on the economic growth of Zimbabwe using data collected from 1995 to 2018. The study further assessed whether the impact was realisable in the short-run or in the long-run. The results from the cointegration test and the causality test show that Diaspora Remittances have a long-run causal impact on economic growth in Zimbabwe. The results also show that the causal impact is unidirectional running from remittances to economic growth. In the short-run, the results reflected that remittances were failing to have a significant impact on the country's economic growth. These findings thus suggest that the nation of Zimbabwe requires complete and concise solutions to drive the country's economic growth. Particular attention should be paid to the country's growth enhancers in the long-term like diaspora remittances. The policy-makers should strive to develop a strong institutional framework that facilitates the channeling of remittances to productive uses. Finally, the policy-makers should craft policies that aim at increasing the diaspora remittances inflows through formal channels as one of the measures to enhance sustainable economic growth of the country.